Prevalence of circulating tumor cells in early breast cancer patients 2 and 5 years after adjuvant treatment - Bauer, Emanuel Christoph Alexander; Schneeweiss, Andreas (Breast cancer research and treatment, 2018)
Purpose: Several studies have provided evidence on the prognostic relevance of circulating tumor cells (CTCs) detected before and after chemotherapy regarding overall survival (OS) and progression-free survival (PFS) in early breast cancer (EBC). We provide data on the prevalence of CTCs 2 and 5 years after primary diagnosis in a cohort of patients with EBC.Methods: The SUCCESS study is a multicenter, prospective, randomized trial comparing PFS in primary breast cancer patients undergoing one of two adjuvant chemotherapy regimens followed by 2 versus 5 years of treatment with zoledronate. CTCs from patients without signs of breast cancer recurrence were analyzed in peripheral blood using the FDA cleared CellSearch® System (Veridex, USA) 2 and 5 years after primary diagnosis. Results: CTCs were detected at 2 and 5 years after primary diagnosis in 96 (16.7%) and 47 (8.2%) of the 574 patients, respectively. There were no associations between CTC status and patient and tumor characteristics or treatment regimens. In 442 (77.0%) patients, no CTCs were detected at either of the two time points, and in 11 patients (1.9%), CTCs were found at both 2 and 5 years after primary diagnosis. In 85 (14.8%) patients, CTCs were present 2 years after primary diagnosis but not after 5 years, while 36 (6.3%) patients had CTCs in their blood only at the 5-year follow-up. Conclusions: In patients with EBC, CTCs can be detected even 5 years after primary diagnosis without clinical signs of disease recurrence.
Gesehen am 05.03.2020